Phytochemicals and Biological Properties of Azorean Camellia sinensis Black Tea Samples from Different Zones of Tea Plantation - Lisete Sousa Paiva; Ana Paula Dias; Madalena Hintze Motta; José António Bettencourt Baptista (Plants)
Camellia sinensis tea has received considerable attention due to its beneficial effects on health, particularly due to its antioxidant properties that are affected by several factors, which have a high influence on the final quality of black tea. The objective of this study was to investigate the biological properties of Azorean C. sinensis black tea from five different zones of tea plantation in order to select specific areas to cultivate tea rich in targeted compounds beneficial to human health. The free radical scavenging activity (FRSA), ferric reducing antioxidant power (FRAP), ferrous ion chelating (FIC) activities, total phenolic content (TPC), total flavonoid content (TFC), and tannins were determined by colorimetric methods, and catechin and theaflavin contents were analyzed by high-pressure liquid chromatography. The results indicated that samples from Zone E (341 m above the sea level) presented higher values of FRSA (EC50 = 7.22 µg/mL), FRAP (EC50 = 9.06 µg/mL), and FIC activities (79.83%) and higher values of total phenolics (264.76 mg GAE/g DE) and almost all catechins. For TFC, the values were very similar between zones, and for theaflavins content, Zone A showed the best levels, followed by Zone E. In general, these results clearly highlight that altitude plays a significant role in enhancing certain compounds of tea, thereby influencing its quality.